GE_GERICHTE P/5177/2017 vom 10. Januar 2020 - GE Cour de justice (2020)
HOMICIDE PAR NÉGLIGENCE;CIRCULATION ROUTIÈRE(DROIT DE LA CIRCULATION ROUTIÈRE);POIDS LOURD;PIÉTON | CP.117; CP.12; LCR.26; LCR.49